LIBRARY DIGITIZATION AS AN EFFORT TO PRESERVE ISLAMIC LITERACY: A STUDY AT THE NORTH SUMATRA MUI LIBRARY - Zalika Dwi Ayunda; Adenan Adenan; Abdillah Rizki Tanjung; Aldi Firmansyah (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2026)
This study aims to examine library digitization as a strategy for preserving Islamic literacy and to analyze its implementation and impact on access and preservation of collections at the Library of the Majelis Ulama Indonesia (MUI) of North Sumatra. This research employs a qualitative descriptive approach using observation, documentation, and the authors’ empirical experience during an internship at the MUI of North Sumatra Library. The findings indicate that the digitization process involves the conversion of physical collections into digital formats, thematic classification of digital materials, and the use of digital storage platforms to facilitate information access. However, several challenges remain, including limited technological infrastructure, human resource capacity, and institutional support. This study concludes that the digitization of the MUI of North Sumatra Library plays a strategic role in preserving and disseminating Islamic literacy, although further strengthening of infrastructure, policies, and human resources is required to ensure sustainability.